2016
DOI: 10.1007/s10029-016-1513-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of inflammatory response and collagen morphometry with different types of meshes

Abstract: Inflammation scores decreased in all groups at 28 POD. Collagen deposition was higher for non-composite meshes at 28 POD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…It is questioned whether at a later time, as Maeda et al . 20 described, this process of tissue inflammation could reduce and fibroplasia could improve, respectively, with the reduction of the inflammatory cellularity and maturation of the deposited collagen, which is consistent with the foreign body reaction that characterizes the implantation of synthetic meshes in the repair of hernias and abdominal wall defects.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…It is questioned whether at a later time, as Maeda et al . 20 described, this process of tissue inflammation could reduce and fibroplasia could improve, respectively, with the reduction of the inflammatory cellularity and maturation of the deposited collagen, which is consistent with the foreign body reaction that characterizes the implantation of synthetic meshes in the repair of hernias and abdominal wall defects.…”
Section: Discussionsupporting
confidence: 66%
“…Maeda et al . 20 , in a study with intraperitoneal implantation of polypropylene mesh with and without absorbable polydioxanone anti-adhesive barrier, concluded that a lightweight and macroporous polypropylene mesh favors an early more intense inflammatory reaction than the heavy-weight and microporous polypropylene mesh. Because it allows a greater flow of cells through the pores in this phase of prosthesis incorporation, which in turn contributes to a better collagen deposition and maturation at a later stage as the intensity of inflammation gets lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pascual et al 37 also demonstrated that the use of meshes containing absorbable biological materials could increase the production of inflammatory mediators. Maeda et al 38 compared four different types of mesh: high-density PP, low-density PP, PP mesh encapsulated with oxidized cellulose-coated PDO, and expanded polytetrafluoroethylene. On postoperative day 28, the inflammatory scores of the low-density PP group were lower than those of all other groups 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Maeda et al 38 compared four different types of mesh: high-density PP, low-density PP, PP mesh encapsulated with oxidized cellulose-coated PDO, and expanded polytetrafluoroethylene. On postoperative day 28, the inflammatory scores of the low-density PP group were lower than those of all other groups 38 . Our work also suggests that the use of absorbable biological materials, such as PDO, can prolong the inflammatory tissue reaction compared to PP.…”
Section: Discussionmentioning
confidence: 99%